1976
DOI: 10.1159/000251104
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Lymphocyte Function in Behçet’s Disease

Abstract: Aspects of lymphocyte function were investigated, in vitro, in nine patients with active Behçet’s disease. The rosette formation technique revealed a slight decrease in number of T lymphocytes and more so of B lymphocytes. In spite of their low number, the transformation of the T lymphocytes in response to mitogens did not show a significant difference from that of normal controls. This may indicate a hyperreactivity, and in two instances a spontaneous blastogenesis prior to addition of mitogens, was also note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In our investigations, we found that the percentage of T lymphocytes was increased in patients with active BD. This is in sharp contrast to past studies [10,11,[13][14][15][16]] that reported either normal or low values and supports the findings of the Haim et al [12] group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our investigations, we found that the percentage of T lymphocytes was increased in patients with active BD. This is in sharp contrast to past studies [10,11,[13][14][15][16]] that reported either normal or low values and supports the findings of the Haim et al [12] group.…”
Section: Discussionsupporting
confidence: 80%
“…Naubiki et al [10] as well as Djawari et al [11] have noted normal B and T lymphocytes in the peripheral blood. On the other hand, Haim et al [12] claimed that B lymphocytes are abnormally decreased while T lymphocytes are proportionately increased. The vast majority of investigations found a decreased number of total peripheral T lymphocytes and a decreased T cell helper to suppressor ratio [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…To these features we may add the normal transformation of T lymphocytes in response to mitogens in comparison with controls inspite of their decreased number as revealed in a previous study conducted in our department [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, the criteria postulated so far for such mechanism in this process are not beyond any doubt [5,6]. We thought, therefore, that further information in this concern may be provided by a study of leucocyte migration inhibition (LIF) in patients with this malady.…”
mentioning
confidence: 99%
“…Heim et al [8] studied aspects of lymphocyte functions in 9 Behcet syndrome patients and reported decreased levels of T and B cells with normal blastogcnic response to PHA, PPD, SK.SD and Candida. According to their technique, their B cells were actually EA rosettes or Fc receptor-bearing cells and not pure B cells or Smlg-bearing cells.…”
Section: Discussionmentioning
confidence: 99%